2011
DOI: 10.1089/neu.2011.1836
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Changes in Diffusivity Measures after Sports Concussion

Abstract: Despite negative neuroimaging findings in concussed athletes, studies indicate that the acceleration and deceleration of the brain after concussive impacts result in metabolic and electrophysiological alterations that may be attributable to changes in white matter resulting from biomechanical strain. In the present study we investigated the effects of sports concussion on white matter using three different diffusion tensor imaging (DTI) measures: fractional anisotropy (FA), mean diffusivity (MD), and axial dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
192
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(229 citation statements)
references
References 67 publications
31
192
2
4
Order By: Relevance
“…While many of these findings were sex‐dependent and are discussed further in the next section, DTI metrics revealed a significant effect of injury in the contralateral CC with RmTBI rats having significantly lower AD and ADC than shams regardless of sex. Reduced ADC has been observed in the CC of adolescents with mTBI,48 and in university students including concussed male49 and female50 athletes. In the latter study, and consistent with our results here, concussed athletes also had reduced AD in the CC.…”
Section: Discussionmentioning
confidence: 95%
“…While many of these findings were sex‐dependent and are discussed further in the next section, DTI metrics revealed a significant effect of injury in the contralateral CC with RmTBI rats having significantly lower AD and ADC than shams regardless of sex. Reduced ADC has been observed in the CC of adolescents with mTBI,48 and in university students including concussed male49 and female50 athletes. In the latter study, and consistent with our results here, concussed athletes also had reduced AD in the CC.…”
Section: Discussionmentioning
confidence: 95%
“…78 In discussing these findings, other researchers 68 suggest the possibility that contact sport athletes represent a distinct population because of their continued exposure to subconcussive hits leading to constant WM injury and recovery cycles and therefore might present a different recovery profile from the civilian, non-contact-sport population suffering a single mTBI episode. It must be noted that at least one study on SRC 79 showed significantly higher FA, AD, and lower MD (as compared to noncontact controls) values at two time points: *81 hours (on average) and 6 months postinjury, suggesting no significant recovery in diffusion measures during that time interval. Future work is needed to address these observed differences of diffusion metrics during recovery after SRC.…”
Section: Longitudinal Dti Study Of Wm Tracts After Srcmentioning
confidence: 96%
“…In 2012, a systematic review of the DTI and concussion literature [65] reported on eight studies and raised concern in the literature at the time that there was so much variability in the methodology bringing together the findings of the diverse range of work and attempting to interpret the results was challenging. A more recent DTI and concussion systematic review [49] suggested that the most consistent findings were decreased mean diffusivity and/or an increase in fractional anisotropy in white matter within 6 months post-concussion [66][67][68][69][70], but these findings are not universal (i.e., the opposite patterns have also been reported in other studies) [56,62,71]. In addition, reduced radial diffusivity has been reported [68,[72][73][74], but increase and decrease in axial diffusivity have been described [68,69].…”
Section: Neuroimagingmentioning
confidence: 92%